1992
DOI: 10.1007/bf02050532
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the predictive accuracy of goodsall's rule for anal fistulas

Abstract: To examine the predictive accuracy of Goodsall's rule, the records of 216 patients (155 men and 61 women) who underwent surgery for complete submuscular anal fistulas from 1982 to 1989 were retrospectively reviewed. In accordance with Goodsall's rule, 90 percent of 124 patients with an external opening posterior to the transverse anal line had anal fistulas tracking to the midline (87 percent men and 97 percent women). Only 49 percent of the 92 patients with an external opening anterior to the transverse anal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 1 publication
2
30
1
5
Order By: Relevance
“…To date, the studies done to assess the predictive accuracy of the Goodsall's rule have shown conflicting results [1,4,5]. According to a retrospective study of 216 patient records conducted in the 1980s, the predictive accuracy for fistulae with external openings posterior to the transverse anal line was 90% while for those with external openings anterior to the transverse anal line was 49% [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the studies done to assess the predictive accuracy of the Goodsall's rule have shown conflicting results [1,4,5]. According to a retrospective study of 216 patient records conducted in the 1980s, the predictive accuracy for fistulae with external openings posterior to the transverse anal line was 90% while for those with external openings anterior to the transverse anal line was 49% [1].…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of both external and internal openings of the fistula tract is necessary for complete identification of the course of the tract. Identification of the external opening is obvious as the patient presents with a discharge through the external opening, but identification of the internal opening may not be straight forward [1]. Several classification systems exist to help clinicians to identify the path of the tract.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The popular Goodsall's rule for predicting the trajectory of anal fistulas is widely applied; however, in clinical practice, some cases are incompatible with this rule 1,2) . According to this rule, a transverse line is firstly drawn across the anus.…”
Section: Discussionmentioning
confidence: 99%
“…Goodsall's rule for predicting the trajectory of anal fistulas is popular; however, the long-tract anterior fistula, which may also include fistulas with scrotal extension, is an exception of this rule 1,2) . To the best of our knowledge, the rules applicable to anal fistulas with scrotal extension and the suitable operative treatment are yet to be described in detail.…”
Section: Introductionmentioning
confidence: 99%